Knowledge integration capability, innovativeness, and entrepreneurial orientation on business performance - Helisia Margahana; Dyah Sugandini (Jurnal Konseling dan Pendidikan, 2022)
Objectives – This study aims to analyze the business performance of SMEs in South Sumatera, which has limited resources and is affected by the COVID-19 pandemic but can still survive. The business performance is analyzed through knowledge integration capability, innovativeness, and entrepreneurial orientation.Design/methodology/approach – The research method used is a questionnaire survey, and the respondents observed were 232 SMEs in South Sumatra. The data analysis technique uses a two-step approach to SEM with SEM-AMOS 25.Findings – The Business Performance Model is acceptable. Furthermore, business performance is influenced by knowledge integration capability, innovativeness, and entrepreneurial orientation. The more SMEs that have a strong entrepreneurial orientation can integrate the knowledge of their employees and have the ability to adopt innovation (innovativeness) quickly, SMEs can improve their performance, even in difficult times due to the COVID-19 pandemic.Research limitations/implications – This study only observed SMEs that survived the COVID-19 pandemic and did not involve SME respondents who failed to adapt to the pandemic. This study only uses knowledge integration capability, innovativeness, and entrepreneurial orientation in predicting performance. The ability to integrate knowledge has a relatively small impact on the performance of SMEs, and it is better if the influence of this knowledge can be analyzed further to get better results.Originality/value – This study adds entrepreneurial orientation as a determinant of the ability to integrate knowledge in one model analyzed to predict SMEs' performance after the COVID-19 pandemic. The respondents of this research are also SMEs that have been affected by COVID-19 and are still surviving now.